If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29y + 56 = 27 Reorder the terms: 56 + 29y = 27 Solving 56 + 29y = 27 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 29y = 27 + -56 Combine like terms: 56 + -56 = 0 0 + 29y = 27 + -56 29y = 27 + -56 Combine like terms: 27 + -56 = -29 29y = -29 Divide each side by '29'. y = -1 Simplifying y = -1
| 3x^2+5x^2+4x-2x^3-3x^2-x= | | (2x)+(3x-10)=65 | | t+7=0 | | -2+5y=-5 | | 2x+14=-74-4x | | 10c-51=7 | | 3(x+y+z)= | | -5-3x=14-10x | | 6x-2x+5y-3x= | | 8x^2-10-18=0 | | 3x+9=3(x-6) | | 55-3x=8 | | 5xy^2+2xy^2= | | x-1=42 | | 6z-3z= | | 2(7x-3)=36 | | -3=v-5 | | 3x-6+6x-2=-23+6x | | 0.6x+4.9=1.6 | | -v^2-2v+30=0 | | 8(4d-7)= | | 5x^2-7x+3= | | 8=v-1 | | 5(8c+4)= | | 2x(x+48)=500 | | 6x+8+5x=8x-10 | | 2x+x+48=500 | | 3(b-5)= | | x*x+1*x-15.75=0 | | 4(3b-5)+2b= | | c=2.50(n-2)+4.50 | | 5b^2+b+1=0 |